تماشي عروض التكوين في معاهد علوم وتقنيات النشاطات البدنية والرياضية مع سوق العمل من وجهة نظر الأساتذة - قسم التربية البدنية نموذجا– - قاسمي فريد; Supervisor د. ابن دقفل رشيد (Mohamed Boudia University of M'sila, 2024)
الملخص : تهدف هذه الدراسة الى معالجة اشكالية الدراسة المتمثلة في مدى تماشي عروض التكوين مع متطلبات سوق العمل، لمعالجة الموضوع تم الاعتماد على المنهج الوصفي من خلال استعراض الادبيات المتعلقة بمتغيرات الدراسة والمتمثلة في سوق العمل والتكوين، كما تم الاعتماد على اداة الاستبيان المتمثل في محور متعلق بالبيانات الشخصية ومحور متعلق بتماشي عروض التكوين مع سوق العمل ومحور متعلق بجوة عروض التكوين، حيث تم توزيع الاستبيان على عينة مكونة من 20 استاذ بمعهد العلوم وتقنيات نشاطات التربية البدنية والرياضية وتم الاعتماد على برنامج SPSS في استعراض البيانات الوصفي واختبار فرضيات الدراسة، وتوصلت الدراسة الى ان عروض التكوين بمعهد تتسم بجودة عالية ، وتؤكد نتائج الدراسة على ان عروض التكوين تتماشى مع متطلبات سوق العمل. عنوان الدراسة : تماشي عروض التكوين في معاهد علوم وتقنيات النشاطات البدنية والرياضية مع سوق العمل من وجهة نظر الأساتذة - قسم التربية البدنية نموذجا– أهداف الدراسة : - . تسليط الضوء على عروض التكوين الأكاديمي بمعاهد علوم وتقنيات النشاطات البدنية والرياضية وهل تتماشى مع متطلبات سوق العمل. - التعرف على ما مدى عروض التكوين الأكاديمي بمعاهد علوم وتقنيات النشاطات البدنية والرياضية في ضوء متطلبات سوق العمل. التساؤل العام الدراسة: هل تتماشى عروض التكوين الأكاديمي لطلبة معهد علوم وتقنيات النشاطات البدنية و الرياضية مع متطلبات سوق العمل؟. التساؤلات الجزئية : 1- ما مدى جودة عروض التكوين في معاهد علوم وتقنيات النشاطات البدنية و الرياضية ؟ 2- ما مدى استجابة سوق العمل لخريجي معاهد علوم وتقنيات النشاطات البدنية والرياضية ؟ الفرضية العامة للدراسة : نعم تتماشى عروض التكوين مع متطلبات سوق العمل. الفرضيات الجزئية 1- تتسم عروض التكوين الأكاديمي بجودة عالية. المنهج المتبع في الدراسة : المنهج الوصفي التحليلي الأدوات المستخدمة في الدراسة اداة الاستبيان الكلمات المفتاحية بالعربية: الجودة التكوين، سوق العمل جاء هذا البحث في فصول . الفصل الأول: الاطار العام للدراسة وتناول الفصل الثاني: سوق العمل أما الفصل الثالث: التكوين الاكاديمي الفصل الرابع: منهج الدراسة الفصل الخامس: عرض وتحليل النتائج ومناقشتها. من أهم النتائج التي توصل إليهاالباحث : • ان عروض التكوين بمعهد علوم وتقنيات نشاطات التربية البدنية والرياضية بجامعة المسيلة تتماشى مع متطلبات سوق العمل • ان عروض التكوين بمعهد علوم وتقنيات نشاطات التربية البدنية والرياضية بجامعة المسيلة تتسم بجودة عالية Searchlight in English Faculty Institute of Sciences and Sports and Technical and PhysicalActivities Department: Order No:......................................................... No. d 'registration : ............................................... .................................. Searcher : gasmi farid Publicly supported on :............................................................................ Title of the thesis (dissertation): In line with the labor market for the first time in institutes of science and technology of sports activities from the point of view of teachers’ rights - the Department of Education is an example - Language of the thesis: Arabic Model of the thesis: Master Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor: Ibn Daqfal Rashid Grade: docteur Lecturer Number of pages: 88 Option: Questionnaire Summary: This study aims to address the problem of the study, represented by the extent to which training offers are consistent with the requirements of the labor market. To address the issue, the descriptive approach was relied upon by reviewing the literature related to the variables of the study, namely the labor market and training. Also, reliance was placed on the questionnaire tool represented by an axis related to personal data. An axis related to the compatibility of training offers with the labor market, and an axis related to the atmosphere of training offers. The questionnaire was distributed to a sample of 20 professors at the Institute of Science and Technology for Physical Education and Sports Activities. The SPSS program was relied upon to review descriptive data and test the study’s hypotheses. The study concluded that training offers The institute is characterized by high quality, and the results of the study confirm that the training offers are in line with the requirements of the labor market. Title of the study: In line with the labor market for the first time in institutes of science and technology of sports activities from the point of view of teachers’ rights - the Department of Education is an example -. The purpose of the study:. -. Highlighting the academic training offers at the institutes of science and technology of physical and sports activities and whether they are compatible with the requirements of the labor market. - Identifying the extent of academic training offers at institutes of science and technology of physical and sports activities in light of the requirements of the labor market. Problem: Are the academic training offers for students of the Institute of Science and Technology of Physical Activities and Sports in line with the requirements of the labor market? Hypotheses: 1. Yes, training offers are in line with labor market requirements. 2. The academic training offers are of high quality Key words : professional formation، Labor market - The most important results achieved are: • The Institute of Science and Technology should provide physical education activities in M’sila in line with the requirements of the labor market • The Institute of Science and Technology provides sports educational activities in M’sila, but with high quality
Keywords: الجودة التكوين; سوق العمل